Gross Osteology, Radiographic and Computed Tomographic Morphology of the Axial Skeleton of the Nine‐Banded Armadillo (Dasypus novemcinctus). (9th September 2016) - Alves, L. S.; Midon, M.; Filadelpho, A. L.; Vulcano, L. C.
Summary: This study used 20 nine‐banded armadillo, four in vivo and 16 cadavers, to describe the osteoarticular anatomy of the axial skeleton by means of digital radiography and computed tomography. Vertebral formula obtained in this sample specimens was seven cervical, 10 thoracic, five lumbar, nine vertebrae related to the synsacrum and 20–27 free caudal vertebrae. Peculiar features of this species were noted as the presence of xenarthrous processes in the caudal thoracic vertebra to the last lumbar vertebra, with prominent mammillary processes in the thoracolumbar segment, fused cervical vertebra from the second to fourth vertebra and the presence of synsacrum related to sacral and caudal vertebra fused to the pelvis. They are homodont animals presenting only molariform teeth with formula of 8/8, totalling 32 teeth. There was no complexity in the execution of radiographic and tomographic examinations, concluding that execution can be carried out in nine‐banded armadillos during the clinical routine for wild animals.